Analysis of return period and seismic risk of Shallow Earthquake occurrence in Cianjur and surrounding areas - sutrisno, sutrisno; Tjahjono, Arif; Putra, Fathin Ramadhan (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
Determination of the seismic risk and return period of shallow earthquakes in Cianjur and surrounding areas is very important as a reference in earthquake disaster mitigation programs. Within this return period, structural and non-structural conditions can be prepared in stages that are ready to face disasters if the earthquake recurs. In this study used the least squares statistical method to determine the relationship between frequency and magnitude, level of risk, and earthquake return period. The earthquake data used in this study is sourced from the earthquake catalog of the United States Geological Survey (USGS) spanning 50 years (1973 – 2023). A total of 57 shallow earthquakes that occurred in Cianjur area and its surroundings at coordinates (06°-08°S and 106°-108°E) with magnitude greater or equal to 5.0 at a depth of 0-60 km were used as sample data. Based on the results of data processing and analysis, the return periods are 3.17 to 29.1 years for earthquakes with magnitudes between 5.0 and 6.0, and 29.1 to 267.38 years for earthquakes with magnitudes between 6.0 and 7.0.. Earthquake risk for 10 to 20 years with magnitude greater than 5.0 is 95.74 to 99.82 %, with magnitude greater than 6.0 is 20.09 to 49.70 %, and with magnitude 7.0 is 3.67 to 7.21 %. From the results of processing and analysis of the earthquake data, it shows that the Cianjur area and its surroundings are earthquake-prone areas with a high risk.